1258. B/F/TAF in HIV-Infected Adults with Substance Use Disorders: BASE Week 48 Results. (15th December 2022) - Havens, Josh; Bares, Sara H; Lyden, Elizabeth; Lyden, Elizabeth; Lyden, Elizabeth; Podany, Anthony; Scarsi, Kimberly; Fadul, Nada; Swindells, Susan
Abstract: Background: People with HIV (PWH) and substance use disorders (SUD) are at higher risk of non-adherence. Bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) exhibits high rates of efficacy with a favorable adverse event profile. The BASE study (NCT03998176) is a Phase 4, single-arm study evaluating the effectiveness and safety of B/F/TAF among PWH and SUD. Methods: Viremic (HIV RNA >1000 copies [c]/mL) treatment-naïve or -experienced PWH and ongoing SUD initiated B/F/TAF once daily for 48 weeks (W). The primary endpoint was HIV RNA < 50 c/mL (FDA Snapshot Algorithm) at W48. Secondary endpoints were safety, adherence (dried blood spot [DBS] levels of emtricitabine-triphosphate [FTC-TP] and tenofovir-diphosphate [TVF-DP]), substance use (NIDA ASSIST) and quality of life (SF-12). Results: Forty-three participants enrolled; 95% reported methamphetamine use. Median age was 38 years (range: 21-62); 19% female, 81% White, 14% Black, 16% Latinx. At W48, 21 participants (49%) had HIV RNA < 50 c/mL (ITT, Figure 1). Four participants (9%) experienced confirmed virologic failure; none developed treatment-emergent resistance. Seventeen participants (40%) experienced grade ≥3 adverse events; none attributed to B/F/TAF. Five participants reported suicidal ideation; none resulted in discontinuation. Observed mean FTC-TP and TVF-DP concentrations in DBS corresponded to 5-6 doses/week (FTC-TP: >3.6 pmol/7mm punches; TVF-DP: >1733 fmol/7 mm punches; Figure 2). NIDA ASSIST scores declined from baseline, with methamphetamine use decreasing most (-7.9 points; -29%). SF-12 physical/mental scores increased 1.2 and 7.6 points, respectively, but remained below mean US scores. Longitudinal virologic outcomes, intent-to-treat analysis Mean observed intracellular emtricitabine triphosphate (FTC-TP) and tenofovir diphosphate (TFV-DP) in dried blood spots at weeks 6, 24, and 48 Thresholds for 2-3 doses/week (Solid Line) and 4-5 doses/week (Dashed Line) are noted for both FTC-TP and TFV-DP based on TAF-DBS data [Yager J, et al. JAIDS, 2020]. Notes: Y-axis represents femtomoles/punches Conclusion: B/F/TAF among a high-risk population of PWH and ongoing SUD resulted in a 49% viral suppression rate at W48. No emergent resistance was noted supporting the high barrier to resistance provided by B/F/TAF. Disclosures: Sara H. Bares, MD, Gilead Sciences: Expert Testimony|GSK ViiV Healthcare: Grant/Research Support|Janssen: Grant/Research Support Kimberly Scarsi, PharmD, Organon: Grant/Research Support.